The Use of AI Agents to Help Teach IELTS Writing Task 2: A Narrative Inquiry - Rizki, Muhammad; Anjarningsih, Harwintha Yuhria (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
This study explores the experience of an English teacher using AI agents to teach IELTS Writing Task 2. Using a narrative inquiry approach, it delves into how AI agents enhance students' writing skills, specifically in IELTS preparation classes, and the challenges faced by the instructor in the process. Findings indicate that AI agents, such as ChatGPT, play a significant role in providing personalized feedback, supporting autonomous learning, and optimizing class time. However, AI use also presents challenges, including risks of over-reliance, academic integrity concerns, and feedback accuracy. The study highlights the importance of careful guidance and institutional policies to ensure ethical and effective AI usage in education. The research implications include a need for further investigation into AI’s specific applications for test preparation, which could enhance instructional strategies for high-stakes exam preparation like IELTS.